Intravascular metastatic melanoma: A difficult diagnosis. (21st February 2013) - Ghattas, Samer; Howle, Julie; Wang, Wei; Kefford, Richard; Gruenewald, Simon
Abstract Melanoma is a common cancer with the potential for widespread metastasis; however intravascular metastasis is extremely rare. We report an unusual case of a patient with metastatic melanoma in whom 18F‐fluorodeoxyglucose positron emission tomography‐computed tomography (FDG PET‐CT) demonstrated an intravascular melanoma metastasis in the superior vena cava (SVC), successfully treated with external beam radiotherapy. To our knowledge, this is the first reported case where FDG PET‐CT was used to make this diagnosis.